HOW TO IMPROVE SPEAKING COMPETENCE IN EFL CLASSROOMS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article deals with a number of scientific considerations about further improving the speech skills of students in English classes.